Periorbital lipogranuloma: a previously unknown complication of autologous fat injections for facial augmentation. Issue 9 (1st November 2010) - Sa, Ho-Seok; Woo, Kyung In; Suh, Yeon-Lim; Kim, Yoon-Duck
Abstract : Background: Autologous fat injection into the face is a commonly used technique in plastic surgery. Autologous fat is claimed to be a safe soft-tissue filler without a foreign body reaction. This article reports on several cases of periorbital lipogranuloma after autologous fat injection for facial augmentation. Methods: This was a retrospective, non-comparative and interventional case series. The authors identified nine patients with periorbital lipogranuloma. All patients had a history of previous autologous fat injection into the face by different plastic surgeons. A medical record review was performed for clinical history, radiological and histopathological studies, and treatment. Results: Nine patients developed periorbital granuloma after autologous fat injection for facial augmentation. Eight of the patients had received two injections of autologous fat, and seven patients had undergone a second injection with their cryopreserved fat tissue. Erythematous swelling of the upper eyelid was refractory to antibiotic and steroid treatment, and surgery was required to resolve the inflammatory reactions in six cases. Histopathological evaluation revealed features of a lipogranulomatous reaction, with collection of histiocytes and foreign-body type giant cells around variable-sized microcysts containing lipid materials. Conclusions: Lipogranuloma can develop in the eyelid following autologous fat injection to the forehead or glabella. Clinicians should be aware of this potential complication of a granulomatous reaction following autologous fat injection. Techniques for the injection and preservation of autologous fat should be refined.